Red copper foil sheet for electrical flexible connection and preparation process thereof
Through the synergistic effect of multivariate microalloyation and rare earth modification, the composition and process of copper foil sheets are optimized, and the shortcomings of existing materials in welding performance, conductivity and ductility balance and oxidation inclusion are solved, and high conductivity, high ductility and excellent welding performance are achieved, which is suitable for high reliability applications under complex working conditions.
Patent Information
- Application Number
- CN202411818823.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-21
AI Technical Summary
The existing copper foils have shortcomings in welding performance, conductivity and ductility balance and oxidation inclusions in the preparation process, making it difficult to meet the high reliability requirements under complex operating conditions.
Through the synergistic action of multivariate microalloyation and rare earth modification, the components of copper foils are designed, including high-purity copper, phosphorus, silver, zirconium, zinc and rare earth elements, combined with aerosol powdering, hot isostatic molding, cold rolling and annealing and surface treatment processes, to optimize the composition and structure of the material.
The high conductivity, high ductility and excellent welding performance of copper foil are achieved, solving the problems of insufficient softening resistance and poor welding interface performance of traditional materials in high-temperature or high-frequency welding, and improving the overall performance and reliability of the materials.
Smart Images

Figure CN119663042A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials and processing thereof, in particular to a copper foil for electrical soft connection and a preparation process thereof. Background Art
[0002] With the rapid development of electronic equipment, new energy power systems and high-end industries, electrical soft connection materials have put forward higher requirements for high conductivity, high ductility and welding performance. Among them, copper foil has become a key material due to its excellent conductivity and flexibility. The performance and preparation process of copper foil in the existing technology still have limitations, and it is difficult to fully meet the high reliability requirements under complex working conditions.
[0003] The existing copper foil has significant deficiencies in welding performance. Since the composition design mainly relies on a single deoxidizing element (such as phosphorus), it is impossible to effectively remove oxidized inclusions, which leads to easy generation of pores and cracks in the welding area. At the same time, the grain coarsening problem in the high-temperature welding hot zone has not been effectively controlled, affecting the uniformity and mechanical properties of the weld. In addition, the existing materials show obvious lack of softening resistance during high-temperature or high-frequency welding, which limits their application in the field of high-precision welding. There is also a conflict between the conductivity and ductility of the material. It is difficult for the existing copper foil to simultaneously meet the requirements of high conductivity and low hardness.
[0004] Secondly, in terms of preparation technology, the traditional casting and rolling process has problems such as uneven structure, many oxide inclusions, and poor internal density. These process defects directly lead to insufficient mechanical properties and welding adaptability of the material.
[0005] In view of these problems, the present invention proposes a copper foil for electrical soft connection and a preparation process thereof. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a copper foil for electrical soft connection and a preparation process thereof, which solves the problems of welding performance, balance of conductivity and ductility and oxidation inclusion in the preparation process of the prior copper foil.
[0007] To achieve the above object, the present invention is implemented by the following technical scheme: A copper foil for electrical flexible connection, comprising a copper foil made of the following components in weight percentage:
[0008] Base material: high purity copper Cu≥99.95%.
[0009] Phosphorus (P): 0.001% to 0.005%;
[0010] Silver (Ag): 0.01% to 0.05%;
[0011] Zirconium (Zr): 0.002% to 0.01%;
[0012] Zinc (Zn): 0.002% to 0.01%;
[0013] Rare earth elements (Ce and La): 0.001% to 0.005%;
[0014] The balance is copper and unavoidable impurities, of which the oxygen content is ≤0.005%.
[0015] Furthermore, the substrate is high-purity copper (Cu) with a mass fraction of not less than 99.95%, ensuring that the material has excellent electrical conductivity and processing performance; the content of phosphorus (P) is 0.001% to 0.005%, which can effectively reduce the oxygen content in the copper liquid to ≤0.005% as a deoxidizer, reduce the formation of oxide inclusions, and improve the purity and welding performance of the material; the content of silver (Ag) is 0.01% to 0.05%, and its addition can significantly improve the softening resistance of the copper foil in a high-temperature welding environment, prevent grain growth, and enhance the mechanical properties of the welding area; the content of zirconium (Zr) is 0.002% to 0.01%, which can refine the grains to make the material have higher ductility and crack resistance; the content of zinc (Zn) is 0.002% to 0.01%, Improve the wettability of the welding area and optimize the bonding strength of the welding interface; the content of rare earth elements (Ce and La) is 0.001% to 0.005%, and its addition further enhances the deoxidation effect of the material, removes fine impurities, improves the conductivity of the material and the uniformity of the weld, and enhances the reliability of the material under complex welding conditions. The balance is copper and unavoidable impurities, and the oxygen content is strictly controlled at ≤0.005%. This composition design solves the problems of insufficient welding performance, low softening resistance and grain coarsening of traditional copper foil through the synergistic effect of multi-element microalloying and rare earth modification, so that the copper foil has high conductivity, high ductility, excellent welding performance and long-term stability, and is widely used in the field of electrical soft connection of electronic equipment, new energy power systems and other high-end industries.
[0016] Preferably, the rare earth elements are added in the form of rare earth master alloys (Cu-Ce and Cu-La);
[0017] The rare earth elements are used to improve the deoxidation effect of the material, remove oxidation inclusions, and improve welding performance and crack resistance.
[0018] Furthermore, rare earth elements are added in the form of rare earth master alloys, wherein the rare earth master alloys are copper-based rare earth alloys (Cu-Ce and Cu-La). The rare earth master alloys are pre-alloyed with copper to form a uniform and stable master alloy structure, which can effectively reduce the volatilization loss of rare earth elements during the smelting process, while ensuring the uniformity of their dispersion in the copper liquid, thereby significantly improving the deoxidation effect of the melt. Rare earth elements can react with oxygen and inclusions in the melt to generate rare earth oxides and sulfides with low melting points and easy floating, effectively removing oxidized inclusions in the melt and improving the purity of copper-based materials. This not only optimizes the microstructure of the copper foil, but also enhances the stability of the welding area. The introduction of the rare earth master alloy further refines the grain structure, improves the welding performance of the material, reduces the probability of weld crack formation during welding, and enhances the mechanical properties and crack resistance of the welding area, so that the copper foil exhibits better stability and reliability in high-precision welding application scenarios, providing strong technical support for the application of electrical soft connections under complex working conditions.
[0019] Preferably, the addition amount of zinc (Zn) is controlled at 0.004% to 0.008% to improve the wettability of the welding area and the weld quality.
[0020] Furthermore, the addition amount of zinc (Zn) is controlled at 0.004% to 0.008%. This addition amount range is precisely designed to effectively improve the wettability of the welding area while ensuring the overall electrical conductivity and purity of the material, thereby significantly improving the welding performance. The zinc element exists in trace form in the melt and forms an appropriate solubility with the copper matrix. The wettability of the welding pool is enhanced by reducing the surface tension of the melt. This effect is particularly prominent in complex welding processes such as laser welding and high-frequency welding. It can significantly improve the fluidity and filling of the metal in the welding area, thereby making the weld interface more uniform and dense. At the same time, since the zinc element has a certain antioxidant effect, it can effectively reduce the formation of the oxide layer during the welding process, further reduce the incidence of weld defects, and optimize the weld quality and mechanical properties. The optimized zinc content range can also avoid the evaporation loss and tissue embrittlement caused by excessive zinc addition, so that the copper foil has a more stable weld performance while ensuring high welding adaptability, meeting the high-demand welding application requirements under complex industrial conditions.
[0021] Preferably, by controlling the synergistic effect of phosphorus (P) and rare earth elements, the oxygen content is controlled at ≤0.002%, thereby improving the electrical conductivity to ≥58MS / m and the elongation to ≥40%.
[0022] Furthermore, through precise ratios and reasonable process parameter control, the deoxidation and inclusion removal functions of phosphorus and rare earth elements in the melt are fully utilized. Phosphorus mainly reacts with dissolved oxygen in the melt to generate volatile phosphorus oxides, thereby rapidly reducing the oxygen content. At the same time, rare earth elements (such as Ce and La) further react with trace oxygen, sulfur and other impurities in the melt to form rare earth oxides and sulfides with low melting points and easy separation. This synergistic effect can not only more thoroughly remove oxidized inclusions, but also significantly improve the purity of the copper matrix, thereby optimizing the microstructure of the material. , refine the grains, and effectively reduce the obstacles to electron migration, so that the conductivity of the material is improved to ≥58MS / m, meeting the needs of efficient electrical transmission. At the same time, the grain refining effect of rare earth elements combined with the strict control of oxygen content makes the material exhibit excellent ductility, with an elongation of ≥40%. This performance improvement makes the copper foil have higher plasticity and adaptability in complex forming and welding processes, solving the problems of reduced conductivity and insufficient ductility caused by high oxygen content in traditional processes, and providing a more efficient and reliable solution for electrical soft connection applications.
[0023] A preparation process of a copper foil comprises the following steps:
[0024] Melting: Melt the high-purity copper substrate at 1100-1200°C, add phosphorus for preliminary deoxidation, then add silver, zirconium, zinc and rare earth master alloys in sequence for alloying, keep warm and purge with argon to remove oxide inclusions;
[0025] Gas atomization powder making: The alloy melt is sprayed with high-pressure argon gas to form spherical powder with a particle size of 10 to 50 μm, and the oxygen content of the powder is controlled at ≤ 0.02%;
[0026] Hot isostatic pressing: the atomized powder is sintered and densified at 500-700°C and 100-200MPa for 2-4 hours to form a copper billet;
[0027] Continuous casting and rolling: Continuously casting and rolling the dense billet, controlling the casting and rolling temperature at 600-700℃ and the billet thickness at 20-50mm;
[0028] Cold rolling and annealing: Through multiple cold rolling, the billet is rolled to a target thickness of 0.1-1.0 mm, during which intermediate annealing (450-550°C, hydrogen protection) is performed, and the final annealing temperature is 250-300°C;
[0029] Surface treatment: The final foil is electrochemically cleaned to remove oxides and a Sn or Ag coating is applied to improve solder wetting.
[0030] Furthermore, smelting is first performed, and the high-purity copper substrate is melted at 1100-1200°C. Preliminary deoxidation is performed by adding 0.001%-0.005% phosphorus. Phosphorus reacts with oxygen in the copper liquid to form volatile oxides, which effectively reduces the oxygen content. Then silver, zirconium, zinc and rare earth master alloy (Cu-Ce or Cu-La) are added in sequence for alloying. The proportion of each added element is precisely controlled and uniformly dispersed in the copper liquid in a fully stirred manner. Silver improves high-temperature softening resistance, zirconium refines grains and enhances ductility, zinc improves welding wettability, and rare earth elements further deoxidize and remove impurities. Then the melt is kept warm. The argon gas is blown under low pressure to completely remove the oxide inclusions and ensure the purity of the melt; then the atomization powder is made, and the alloy melt is atomized by high-pressure argon injection to form a spherical powder with a uniform particle size of 10 to 50 μm. The argon pressure and nozzle diameter are strictly controlled during the atomization process to make the powder surface smooth and without obvious oxidation. The oxygen content of the powder is controlled at ≤0.02% to ensure the density and conductivity of the subsequent process; then the hot isostatic pressing step is entered, the atomized powder is loaded into a sealed mold and sintered under the conditions of 500 to 700 ° C and 100 to 200 MPa. The powder particles are kept at high temperature for 2 to 4 hours. Gradually compact and densify under high pressure to form a copper billet with no pores and uniform structure; then the dense billet is continuously cast and rolled, the casting and rolling temperature is controlled at 600-700℃, and the billet is rolled into a preliminary strip with a thickness of 20-50mm by double-roll rapid cooling technology. In this process, the cooling rate is strictly controlled to avoid grain growth and improve the flatness of the billet surface; in the cold rolling and annealing steps, the strip thickness is gradually reduced to a target thickness of 0.1-1.0mm through multiple cold rolling passes, and the reduction rate of each pass is controlled between 20% and 30% to reduce the occurrence of work hardening. At the same time, intermediate annealing is performed during the rolling process. The annealing temperature is controlled at 450-550°C, and hydrogen is used to protect the environment to prevent oxidation. The final annealing temperature is controlled at 250-300°C to further soften the material to ensure the ductility and low hardness of the foil. Finally, surface treatment is carried out, and the final foil is electrochemically cleaned, and the surface oxides and impurities are removed by a weak acid solution. Then a layer of Sn or Ag coating with a thickness of 10-50nm is applied. The coating enhances the wettability of the foil surface and the weld bonding quality during the welding process, so that the prepared copper foil has excellent conductivity, high ductility and good welding adaptability, and is widely used in high-end application scenarios of electrical soft connections.
[0031] Preferably, in the aerosol powder making step, a nozzle diameter of 2.0 to 3.0 mm is used and the argon pressure is controlled at 0.6 to 0.8 MPa to ensure that the powder particle size is uniform and the oxygen content is stable at ≤0.02%.
[0032] Preferably, in the hot isostatic pressing step, the sealed mold is evacuated to remove air, and surface machining is performed after molding to improve the dimensional accuracy and surface quality of the blank.
[0033] Preferably, the continuous casting and rolling process adopts a rapid cooling process with a cooling rate of ≥50K / s to avoid grain coarsening and improve material structure uniformity.
[0034] Preferably, the reduction rate of each pass in the cold rolling process is controlled at 20% to 30% to prevent the material from hardening and maintain good ductility.
[0035] Preferably, in the surface treatment step, oxides are removed by electrochemical cleaning, and a Sn or Ag coating with a thickness of 10 to 50 nm is applied to improve the wettability of the welding interface and the quality of the weld.
[0036] Furthermore, in the atomization powder making step, a precision nozzle with a nozzle diameter of 2.0 to 3.0 mm is used, and the argon pressure is controlled between 0.6 and 0.8 MPa. By strictly controlling the injection parameters, the alloy melt is stably dispersed into spherical powders with uniform particle size by high-pressure argon gas during the atomization process. The powder surface is smooth and has no obvious oxidation. At the same time, the high-purity argon environment can effectively isolate oxygen contact, inhibit the oxidation reaction of the powder, and stably control the oxygen content at ≤0.02%, ensuring that the powder has excellent purity and density; preferably In the hot isostatic pressing step, the aerosolized powder is first loaded into a sealed mold, and the mold is pumped to a high vacuum state by a high-efficiency vacuum pump to remove air and moisture in the mold to avoid the generation of pores during the molding process. Then, sintering is performed at a temperature of 500 to 700°C and a pressure of 100 to 200 MPa. The powder particles are fully compacted to form a dense blank through a holding time of 2 to 4 hours. After molding, the blank is further subjected to dimensional precision processing and surface flattening processing by surface machining to ensure the dimensional accuracy of the blank. and surface quality meet the requirements of subsequent processing; preferably, the continuous casting and rolling process adopts a rapid cooling process, and the material temperature is quickly reduced by a cooling system with a cooling rate of ≥50K / s during the billet rolling process to avoid grain growth in a high temperature environment, improve the uniformity of the material structure, and ensure the mechanical properties and processing stability of the final strip; preferably, the reduction rate of each pass in the cold rolling process is strictly controlled between 20% and 30%, and the material hardening caused by excessive plastic deformation during processing is prevented by gradually reducing the compression ratio, while maintaining good ductility of the material, so that the final foil has excellent plasticity and welding adaptability; preferably, in the surface treatment step, the oxides and impurities on the surface of the copper foil are removed by a weak acid solution through an electrochemical cleaning process to ensure the cleanliness and uniformity of the material surface, and then a Sn or Ag coating with a thickness of 10 to 50 nm is applied, which effectively reduces the surface tension of the welding interface during welding and improves wettability, thereby enhancing the density and bonding strength of the weld, so that the copper foil can show better performance and reliability in high-precision welding applications.
[0037] The present invention provides a copper foil for electrical flexible connection and a preparation process thereof. The copper foil has the following beneficial effects:
[0038] 1. The present invention ensures that the copper foil has high conductivity, high ductility and excellent welding performance through a composition design scheme of multi-element microalloying and rare earth modification synergistic optimization. Compared with the technical scheme of single element deoxidation or anti-softening treatment in the prior art, the present invention solves the problems of severe oxidation inclusions, grain coarsening and poor welding interface performance in the prior art by reasonably introducing the synergistic effect of phosphorus, silver, zirconium, zinc and rare earth elements, thereby improving the overall performance of the material and being suitable for more complex welding and high-temperature working environments.
[0039] 2. The present invention adopts a preparation process of gas atomization powder preparation combined with hot isostatic pressing to ensure the density and uniformity of the copper billet. Compared with the traditional casting and rolling process in the prior art, which is prone to cause many material inclusions and uneven structure, the present invention generates high-purity spherical powder through high-pressure gas atomization and achieves complete densification under high temperature and high pressure conditions, overcoming the performance degradation problem caused by pores and coarse grains in traditional casting methods, and significantly improving the reliability and service life of the copper foil.
[0040] 3. The present invention achieves high ductility and excellent welding wettability of copper foil by optimizing cold rolling and annealing processes and combining electrochemical cleaning and surface coating technology. Compared with the problems of difficulty in completely eliminating processing stress and insufficient weld wettability in the prior art, the present invention eliminates internal stress by reasonably performing multiple cold rolling and intermediate annealing, and enhances the wettability of the weld interface by combining surface nano-coating technology, thereby solving the problem of frequent welding defects of existing materials in high-precision welding applications and further expanding the application field of copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Please see attached Figure 1 :
[0044] Example 1: Examples with ingredients and preparation process parameters within the range
[0045] Material composition design
[0046] Base material: high purity copper (Cu≥99.95%).
[0047] Phosphorus (P): 0.003%;
[0048] Silver (Ag): 0.03%;
[0049] Zirconium (Zr): 0.005%;
[0050] Zinc (Zn): 0.006%;
[0051] Rare earth elements (Ce and La): 0.003%.
[0052] Preparation process
[0053] Melting: melt the high-purity copper substrate at 1150°C, add phosphorus for preliminary deoxidation, then add silver, zirconium, zinc and rare earth master alloy in sequence, keep warm for 20 minutes, and remove oxide inclusions by argon purge;
[0054] Gas atomization powder making: nozzle diameter is 2.5mm, argon pressure is 0.7MPa, and spherical powder with a particle size of 10-50μm is formed;
[0055] Hot isostatic pressing: powder is sintered at 600℃ and 150MPa, and the pressure is maintained for 3 hours;
[0056] Continuous casting and rolling: casting and rolling temperature is 650℃, billet thickness is 30mm;
[0057] Cold rolling and annealing: the reduction rate for each pass is 25%, the intermediate annealing temperature is 500℃, and the final annealing temperature is 280℃;
[0058] Surface treatment: 20 nm Sn coating was applied after electrochemical cleaning.
[0059] Example 2: Example with ingredients and process parameters below the range values
[0060] Material composition design
[0061] Phosphorus (P): 0.0005%;
[0062] Silver (Ag): 0.005%;
[0063] Zirconium (Zr): 0.001%;
[0064] Zinc (Zn): 0.001%;
[0065] Rare earth elements (Ce and La): 0.0005%.
[0066] Preparation process
[0067] Melting: melt temperature 1080℃, holding time 10 minutes;
[0068] Gas atomization powder making: nozzle diameter 1.8mm, argon pressure 0.4MPa;
[0069] Hot isostatic pressing: powder is sintered at 480℃ and 90MPa, and the pressure is maintained for 1 hour;
[0070] Continuous casting and rolling: casting and rolling temperature 550℃, billet thickness 60mm;
[0071] Cold rolling and annealing: each pass has a reduction rate of 15%, intermediate annealing temperature of 420°C, and final annealing temperature of 220°C;
[0072] Surface treatment: No coating.
[0073] Example 3: Example with ingredients and process parameters above the range values
[0074] Material composition design
[0075] Phosphorus (P): 0.006%;
[0076] Silver (Ag): 0.06%;
[0077] Zirconium (Zr): 0.02%;
[0078] Zinc (Zn): 0.02%;
[0079] Rare earth elements (Ce and La): 0.006%.
[0080] Preparation process
[0081] Melting: melt temperature 1250℃, holding time 30 minutes;
[0082] Gas atomization powder making: nozzle diameter 3.5mm, argon pressure 1.0MPa;
[0083] Hot isostatic pressing: powder is sintered at 750℃ and 250MPa, and the pressure is maintained for 5 hours;
[0084] Continuous casting and rolling: casting and rolling temperature 750℃, billet thickness 10mm;
[0085] Cold rolling and annealing: each pass reduction rate is 40%, intermediate annealing temperature is 600℃, and final annealing temperature is 350℃;
[0086] Surface treatment: 100nm Ag coating was applied.
[0087] Comparative Example
[0088] Comparative Example 1: Lack of rare earth elements
[0089] Material composition design
[0090] Rare earth elements (Ce and La) were not added, and other components were the same as in Example 1.
[0091] Preparation process
[0092] Same as Example 1.
[0093] Comparative Example 2: Lack of Zinc
[0094] Material composition design
[0095] Zinc (Zn) was not added, and other ingredients were the same as in Example 1.
[0096] Preparation process
[0097] Same as Example 1.
[0098] Comparative Example 3: Traditional Casting and Rolling Process
[0099] Material composition design
[0100] Same as Example 1.
[0101] Preparation process
[0102] Using the traditional casting and rolling process, skipping the gas atomization powder making and hot isostatic pressing steps, directly adopting the casting and rolling technology, the casting and rolling temperature is 700℃ and the cooling rate is 20K / s.
[0103] Experimental results comparison table
[0104]
[0105]
[0106] Results Analysis
[0107] High conductivity: The conductivity of Example 1 reaches 58.5MS / m, which is significantly higher than that of other comparison groups, reflecting the advantages of the synergistic deoxidation and densification process of phosphorus and rare earth.
[0108] High ductility: The ductility of Example 1 is 42%, which is about 27% higher than that of Comparative Example 3, proving the importance of zirconium grain refinement and optimization of cold rolling process.
[0109] Excellent welding performance and wettability: The welding performance of Example 1 is significantly better than that of Comparative Examples 1 and 2, which verifies the key role of rare earth elements and zinc elements in improving weld uniformity and wettability.
[0110] Density and structural uniformity: Example 1 significantly improves the density and structural uniformity of the material through gas atomization powder making and hot isostatic pressing process, which is significantly improved compared with Example 3 of traditional casting and rolling.
[0111] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A copper foil for electrical flexible connection, characterized in that: The copper foil is made of the following ingredients in weight percentage: Base material: high purity copper Cu≥99.95%. Phosphorus (P): 0.001% to 0.005%; Silver (Ag): 0.01% to 0.05%; Zirconium (Zr): 0.002% to 0.01%; Zinc (Zn): 0.002% to 0.01%; Rare earth elements (Ce and La): 0.001% to 0.005%; The balance is copper and unavoidable impurities, of which the oxygen content is ≤0.005%.
2. The copper foil for electrical flexible connection according to claim 1, characterized in that: The rare earth elements are added in the form of rare earth master alloys (Cu-Ce and Cu-La); The rare earth elements are used to improve the deoxidation effect of the material, remove oxidation inclusions, and improve welding performance and crack resistance.
3. The copper foil for electrical flexible connection according to claim 1, characterized in that: The addition amount of zinc (Zn) is controlled at 0.004% to 0.008% to improve the wettability and weld quality of the welding area.
4. The copper foil for electrical flexible connection according to claim 1, characterized in that: By controlling the synergistic effect of phosphorus (P) and rare earth elements, the oxygen content is controlled at ≤0.002%, thereby improving the electrical conductivity to ≥58MS / m and the elongation to ≥40%.
5. A process for preparing a copper foil, according to the copper foil for electrical flexible connection according to claims 1 to 4, characterized in that: The following steps are involved: Melting: Melt the high-purity copper substrate at 1100-1200°C, add phosphorus for preliminary deoxidation, then add silver, zirconium, zinc and rare earth master alloys in sequence for alloying, keep warm and purge with argon to remove oxide inclusions; Gas atomization powder making: The alloy melt is sprayed with high-pressure argon gas to form spherical powder with a particle size of 10 to 50 μm, and the oxygen content of the powder is controlled at ≤ 0.02%; Hot isostatic pressing: the atomized powder is sintered and densified at 500-700°C and 100-200MPa for 2-4 hours to form a copper billet; Continuous casting and rolling: Continuously casting and rolling the dense billet, controlling the casting and rolling temperature at 600-700℃ and the billet thickness at 20-50mm; Cold rolling and annealing: Through multiple cold rolling, the billet is rolled to a target thickness of 0.1-1.0 mm, during which intermediate annealing (450-550°C, hydrogen protection) is performed, and the final annealing temperature is 250-300°C; Surface treatment: The final foil is electrochemically cleaned to remove oxides and a Sn or Ag coating is applied to improve solder wetting.
6. The process for preparing a copper foil according to claim 5, characterized in that: In the gas atomization powder making step, the nozzle diameter is 2.0-3.0 mm, and the argon pressure is controlled at 0.6-0.8 MPa to ensure that the powder particle size is uniform and the oxygen content is stable at ≤0.02%.
7. The process for preparing a copper foil according to claim 5, characterized in that: In the hot isostatic pressing step, the sealed mold is evacuated to remove air, and surface machining is performed after molding to improve the dimensional accuracy and surface quality of the blank.
8. The process for preparing a copper foil according to claim 5, characterized in that: The continuous casting and rolling process adopts a rapid cooling process with a cooling rate of ≥50K / s to avoid grain coarsening and improve material structure uniformity.
9. The process for preparing a copper foil according to claim 5, characterized in that: During the cold rolling process, the reduction rate of each pass is controlled at 20% to 30% to prevent the material from hardening and maintain good ductility.
10. The process for preparing a copper foil according to claim 5, characterized in that: In the surface treatment step, oxides are removed by electrochemical cleaning, and a Sn or Ag coating with a thickness of 10 to 50 nm is applied to improve the wettability of the welding interface and the quality of the weld.
Citation Information
Cited By
Copper alloy with excellent high-temperature softening resistance and preparation method and application thereof
CN120519735A